2022
DOI: 10.1021/acsnano.1c10144
|View full text |Cite
|
Sign up to set email alerts
|

An Ultralight Self-Powered Fire Alarm e-Textile Based on Conductive Aerogel Fiber with Repeatable Temperature Monitoring Performance Used in Firefighting Clothing

Abstract: Firefighting protective clothing is an essential equipment that can protect firefighters from burn injuries during the firefighting process. However, it is still a challenge to detect the damage of firefighting protective clothing at an early stage when firefighters are exposed to excessively high temperature in fire cases. Herein, an ultralight self-powered fire alarm electronic textile (SFA e-textile) based on conductive aerogel fiber that comprises calcium alginate (CA), Fe3O4 nanoparticles (Fe3O4 NPs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 43 publications
0
81
0
Order By: Relevance
“…Many early fire-warning studies based on GO have been reported. Likewise, semiconductor materials that possess the special reversible thermally induced conductivity capability can implement the insulator-to-conductor conversion, owning to the charge carrier jump under high-temperature conditions [38,54]. This performance of semiconductor materials exploits an advantage in distinctive recyclable early warning systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many early fire-warning studies based on GO have been reported. Likewise, semiconductor materials that possess the special reversible thermally induced conductivity capability can implement the insulator-to-conductor conversion, owning to the charge carrier jump under high-temperature conditions [38,54]. This performance of semiconductor materials exploits an advantage in distinctive recyclable early warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies on the basis of sulfides and conjugated polymers have been reported. Recently, thermoelectric (TE) materials [55] and triboelectric nano-generators (TENGs) materials [54] are gradually gaining increasing interest, due to their ability to create electrical signals under different conditions, such as the presence of a temperature. The second core is the warning transmission section.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the electrostatic shielding, the overall electric output of the single-electrode TENG is only half of the dual-electrodes mode. However, the advantage of single-electrode TENG affords it a wide range of application prospects in movement monitoring and energy collection of water droplets, intelligent sensing, human-computer interaction and other fields [ 39 , 40 ].…”
Section: The Mechanism and Structure Design Of Tengmentioning
confidence: 99%
“…Yu et al prepared fire-preventing triple-network hydrogels with poly­( N -isopropylacrylamide)/sodium alginate/poly­(vinyl alcohol) and used them to improve the flame retardancy and antibacterial properties of cotton fabrics . Yu and co-workers also used conductive aerogel fibers containing calcium alginate, Fe 3 O 4 nanoparticles, and silver nanowires to prepare ultralight self-powered fire alarm e-textiles . These studies lead us to believe that enhancing the flame retardancy of polymer materials by introducing metal elements is an effective strategy.…”
Section: Introductionmentioning
confidence: 99%
“…37 Yu and co-workers also used conductive aerogel fibers containing calcium alginate, Fe 3 O 4 nanoparticles, and silver nanowires to prepare ultralight self-powered fire alarm etextiles. 38 These studies lead us to believe that enhancing the flame retardancy of polymer materials by introducing metal elements is an effective strategy. However, to our knowledge, the effect of chitosan−metal complexes on the properties of epoxy thermoset materials has not been reported.…”
Section: ■ Introductionmentioning
confidence: 99%